Simmel’s Reification in the Digital Era: The Commodification of Emotional Relationships in Rent-a-Partner Services on Social Media - Pramesti, Juliana (Masyarakat: Jurnal Sosiologi, 2025)
This study examines the commodification of emotional relationships in Indonesia through the rise of “rent-a-partner” services on social media platforms such as Instagram and TikTok. Existing scholarship on digital intimacy has largely focused on Western and East Asian contexts, particularly dating applications, offering limited insight into how commodified intimacy operates in non-Western settings shaped by distinct socio-cultural and moral frameworks. Addressing this gap, the study draws on Georg Simmel’s concept of reification to analyze how emotional intimacy is transformed into purchasable service packages within platform-mediated environments. Using a qualitative approach that combines netnographic observation and in-depth interviews, the study demonstrates that emotional interaction is systematically organized through pricing structures, performative emotional labor, and platform-driven visibility. Platform algorithms not only facilitate but actively shape these services by amplifying emotionally engaging content, aligning affective expression with both market logics as well as socio-cultural expectations, including the management of singlehood stigma and adherence to religious norms. The findings reveal that commodified intimacy is characterized by a persistent tension between authenticity and performativity, where emotional expressions are strategically enacted yet experienced as meaningful. The article thus advances the concept of “moralized commodification,” arguing that reification is negotiated through moral and cultural frameworks rather than driven solely by economic rationality.